Representasi Edukasi Lingkungan untuk Anak dalam Serial Novel Mata Karya Okky Madasari: Perspektif Ekokritik - Galuh Aqmarina Hapsari; Ali Nuke Affandy; Panji Hermoyo (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the representation of environmental education for children in the Mata novel series by Okky Madasari using Greg Garrard’s ecocritical perspective integrated with David W. Orr’s environmental education theory. This research employs a qualitative descriptive method with a library study technique. The data consist of phrases, clauses, sentences, and narrative quotations that reflect ecological elements, environmental pollution, ecological crises, and human–nature relationships. The results show that the Mata series represents nature as a living and interconnected ecological system through the concepts of dwelling, animals, and pastoral. The novels also depict environmental pollution, ecological crises, and natural resource exploitation as consequences of anthropocentric human behavior. Furthermore, the narratives contain strong social and ethical critiques of human dominance over nature, along with forms of resistance that emphasize ecological responsibility. In addition, the series functions as an effective medium for children’s environmental education by fostering awareness, knowledge, attitudes, skills, and participation. Therefore, the Mata novel series serves not only as children’s literature but also as an educational tool to promote ecological awareness.